2022
DOI: 10.3390/nu15010073
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Age-Dependent Changes in the Adiponectin/Leptin Ratio in Experimental Diet-Induced Obesity in Mice

Abstract: Biological sex and aging impact obesity development and type 2 diabetes, changing the secretion of leptin and adiponectin. The balance between these factors has been propounded as a reliable biomarker of adipose tissue dysfunction. Our proposal was to study sexual differences and aging on the adiponectin/leptin (Adpn/Lep) ratio in order to acquire a broader view of the impact of consuming an high-fat diet (HFD) on energy metabolism according to sex and age. Male and female C57BL/6J mice were fed a normal chow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Relatively high serum leptin levels have been reported in obese and female subjects in both clinical and animal studies, 26,46,47 which is consistent with our results (Table 5). The incidence of obesity has been increasing in ESRD patients, and several studies have shown that it is associated with poor VA maturity 29,48 .…”
Section: Discussionsupporting
confidence: 93%
“…Relatively high serum leptin levels have been reported in obese and female subjects in both clinical and animal studies, 26,46,47 which is consistent with our results (Table 5). The incidence of obesity has been increasing in ESRD patients, and several studies have shown that it is associated with poor VA maturity 29,48 .…”
Section: Discussionsupporting
confidence: 93%
“…Fourth, some previous studies including leptin and adiponectin assessments have reported the adiponectin-to-leptin ratio (ALR), [62,63] while others have reported the LAR [41,42,64-66]. We recommend using the more commonly reported LAR versus the ALR.…”
Section: Reporting Issues and Recommendationsmentioning
confidence: 99%
“…iWAT, inguinal white adipose tissue; RAGE229, receptor for advanced glycation end products. *p < 0.05; **p < 0.01 [Color figure can be viewed at wileyonlinelibrary.com] fat mass (Figure 4L); however, plasma adiponectin/fat mass and adiponectin/leptin concentration ratio [17][18][19] were significantly higher in mice fed RAGE229-150 ppm diet versus base diet (Figure 4M,N).…”
Section: Administration Of Rage229-150 Ppm Diet To Adult Lean Male Mi...mentioning
confidence: 99%